Adversity Quotient Generasi Z di Universitas X - Utami, Ni Putu Surya Pradnya; Hardika, I Rai; Septiarly, Yashinta Levy (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2026)
This study explores the level of adversity quotient (AQ) among Generation Z students at Universitas X, Indonesia, who are often labeled as the strawberry generation for being perceived as fragile in facing challenges. The research aims to describe the distribution of AQ and identify differences based on demographic factors such as gender and age. Using a quantitative descriptive approach, data were collected from 356 respondents through a validated questionnaire consisting of 32 items measuring four AQ dimensions: control, origin and ownership, reach, and endurance. The findings reveal a polarized distribution, with the majority of students in the very high (30.1%) and very low (29.2%) categories. Independent samples t-test indicated significant gender differences, with female students showing higher AQ than male students. Moreover, Kruskal–Wallis analysis showed age-based differences, where students aged 19–21 years recorded higher AQ levels compared to older groups. These results highlight the need for targeted interventions to enhance resilience among students with lower AQ.